Artificial Intelligence Robots And Revolutionizing Society In Terms Of Technology, Innovation, Work And Power - Nabila, Efa Ayu; Santoso, Sugeng; Muhtadi, Yudi; Tjahjono, Budi (Pandawan Sejahtera Indonesia, 2021)
In what ways do recent advances in robotics and artificial intelligence signal a historic economic and social transformation? This study presents a critical assessment of the subject, critiques many of the ongoing debates of technical determinism, and reframes the issues involved within a political-economic and social framework. It focuses on technological innovation's economic, political, and historical processes and their implications for employment and financial restructuring, mediated by sovereign and discursive authorities. Several epistemological and empirical issues with a transformational viewpoint are noted, and alternative views are suggested to highlight the complexity and ambiguity surrounding current and future trends. Robotics entered when the industrial revolution had many significant changes for humans. Efficiency is increased to produce various productive things. This paper uses a literature study as a method. The results of his discussion on Revolutionizing Society In Terms Of Technology, Innovation, Work And Power of Robotics.